2018
DOI: 10.3389/fpsyg.2018.00252
|View full text |Cite
|
Sign up to set email alerts
|

Too Depleted to Turn In: The Relevance of End-of-the-Day Resource Depletion for Reducing Bedtime Procrastination

Abstract: Bedtime procrastination is an important predictor of sleep insufficiency in the general population (Kroese et al., 2014b), but little is known about the determinants of this self-undermining behavior. As the phenomenon has been conceptualized in the literature as a form of self-regulation failure (Kroese et al., 2014a), we hypothesized that people’s self-regulatory resources in the evening would be predictive of going to bed later than they intended. Specifically, we examined whether the cumulative effect of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Indeed, a solid body of research has demonstrated significant associations between TP, chronotype and self-regulation. 59,60 Given evidence that BP is robustly associated with chronotype and selfregulation, 3,9,10,61 it appears reasonable for future studies to consider self-regulation in understanding the link between TP and BP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a solid body of research has demonstrated significant associations between TP, chronotype and self-regulation. 59,60 Given evidence that BP is robustly associated with chronotype and selfregulation, 3,9,10,61 it appears reasonable for future studies to consider self-regulation in understanding the link between TP and BP.…”
Section: Discussionmentioning
confidence: 99%
“…The role of procrastination in self-regulation of health behaviors is relatively unknown (Kroese and De Ridder, 2016), but recent research on bedtime procrastination indicates that it may be an important key to understanding self-regulatory failure (Kamphorst et al, 2018; Kroese et al, 2014, 2016; Nauts et al, 2016). Findings from initial studies suggest that bedtime procrastination is associated with poorer sleep outcomes over and above measures of trait self-regulation (Kroese et al, 2014), and that bedtime procrastination prospectively predicts higher discrepancies between planned bedtime and actual bedtime (Kroese et al, 2016).…”
mentioning
confidence: 99%
“…Kühnel et al ( 2018 ) challenge our viewpoint (Kroese et al, 2014 , 2016a ; as well as Kroese et al, 2016b ; Kamphorst et al, 2018 ) that bedtime procrastination—going to bed later than intended without having external reasons for doing so—is a self-regulation problem. They argue that bedtime procrastination is not a self-regulation problem because it is predicted by chronotypes.…”
mentioning
confidence: 99%
“…Finally, a reply is in order regarding perhaps the most striking finding of Kühnel et al's study, namely, that “on evenings on which employees indicated to have more self-regulatory resources at their disposal…employees showed more bedtime procrastination.” To begin with, it should be noted that a recent study suggests the opposite (negative) correlation (Kamphorst et al, 2018 ). The point we wish to emphasize here, however, especially in light of ongoing disputes about resource-based approaches to self-regulation (e.g., Inzlicht and Berkman, 2015 ), is that the self-regulation perspective on bedtime procrastination need not rely on an explanation in terms of the momentary self-regulation resources on which Kühnel et al focus.…”
mentioning
confidence: 99%